Characteristics and Functional Properties of Maillard Reaction Products from α-Lactalbumin and Polydextrose - Kexin Dai; Jiangpeng Wang; Yingting Luo; Yaqi Tu; Fazheng Ren; Hao Zhang (Foods, 2023)
The characteristics and the functions of Maillard reaction products (MRPs) produced by polydextrose (PD), a new type of prebiotic, and α-lactalbumin (α-LA) were valued. PD and α-LA were incubated at 60 °C and 79% relative humidity for up to 72 h to prepare MRPs. The results showed that the absorbance and fluorescence intensity of heated α-LA-PD increased, and the amount of free amino groups reduced as the reaction progressed, which confirmed the formation of different stages of MRPs. Electrophoresis revealed an increase in molecular mass and the degree of covalent cross-linking. The secondary structure of MRPs experienced no significant changes with the measurement of circular dichroism (CD), while the tertiary structure gradually unfolded, exposing hydrophobic groups. Furthermore, a significant increase was detected in the radical-scavenging activity of 2,2-diphenyl-1-picrylhydrazyl (DPPH) and the ferric reducing/antioxidant power (FRAP) of MRPs. The findings offer a foundation for understanding the structural and functional features of MRPs in formula milk powder.